2012
DOI: 10.1159/000337115
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Zinc Superoxide Dismutase (SOD1) Is Released by Microglial Cells and Confers Neuroprotection against 6-OHDA Neurotoxicity

Abstract: Microglial-neuronal interactions are essential for brain physiopathology. In this framework, recent data have changed the concept of microglia from essentially macrophagic cells to crucial elements in maintaining neuronal homeostasis and function through the release of neuroprotective molecules. Using proteomic analysis, here we identify copper-zinc superoxide dismutase (SOD1) as a protein produced and released by cultured rat primary microglia. Evidence for a neuroprotective role of microglia-derived SOD1 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 7,257 publications
(16 citation statements)
references
References 277 publications
1
15
0
Order By: Relevance
“…The first experimental evidence that some cellular lines could be able to secrete the Cu,Zn superoxide dismutase date back to many years ago when we, for the first time, showed the secretion of this protein by experiments performed in hepatocytes and fibroblasts (Mondola et al, 1996), neuroblastoma SK-N-BE cells (Mondola et al, 1998; Gomes et al, 2007; Polazzi et al, 2013) and in thymus derived epithelial cells (Cimini et al, 2002). Interestingly, in further studies we observed the noticeable presence of SOD1 in human serum lipoproteins, mainly in low density (LDL) and high density (HDL) lipoproteins, ascribing to this protein a protective role against the lipoperoxidation (Mondola et al, 2000).…”
Section: Cellular Localization Of Sod1 and Evidences For Constitutivementioning
confidence: 99%
“…The first experimental evidence that some cellular lines could be able to secrete the Cu,Zn superoxide dismutase date back to many years ago when we, for the first time, showed the secretion of this protein by experiments performed in hepatocytes and fibroblasts (Mondola et al, 1996), neuroblastoma SK-N-BE cells (Mondola et al, 1998; Gomes et al, 2007; Polazzi et al, 2013) and in thymus derived epithelial cells (Cimini et al, 2002). Interestingly, in further studies we observed the noticeable presence of SOD1 in human serum lipoproteins, mainly in low density (LDL) and high density (HDL) lipoproteins, ascribing to this protein a protective role against the lipoperoxidation (Mondola et al, 2000).…”
Section: Cellular Localization Of Sod1 and Evidences For Constitutivementioning
confidence: 99%
“…Although SOD1 is predominately localized to the cytoplasm, multiple reports have demonstrated that SOD1 is secreted (Mondola et al, 1996, 1998, 2003; Cimini et al, 2002; Turner et al, 2005). The presence of extracellular SOD1 can in turn increase intracellular calcium levels (Mondola et al, 2004), a phenomena shown to have neuroprotective effects on cerebellar granular neurons exposed to a dopaminergic toxin (Polazzi et al, 2012). This increase in intracellular calcium results from SOD1 activating the phospholipase C/protein kinase C pathway, a pathway implicated in calcium homeostasis (Mondola et al, 2004) through a mechanism involving signal transduction of the muscarinic acetylcholine M1 receptor (M1) (Damiano et al, 2013).…”
Section: Normal Properties and Cellular Functions Of Sod1mentioning
confidence: 99%
“…Microglial cells transfected with human Cu/Zn SOD1, when properly stimulated, are able to release the extracellular isoform of superoxide dismutase into the medium; this antioxidant enzyme in turn protects neurons against 6-OH dopamine-induced cell damage [78]. Accordingly, the exposure of cultured astrocytes to dopamine favored the selective expression of extracellular Cu/Zn-SOD (not SOD 1 or Mn SOD), depending on the dopamine concentration itself (not receptors or metabolism) and nuclear factor kappa-B.…”
Section: Copper-binding Proteins In Parkinson's Diseasementioning
confidence: 99%